1989
DOI: 10.1002/glia.440020507
|View full text |Cite
|
Sign up to set email alerts
|

Expression of beta‐adrenergic receptors by astrocytes isolated from adult rat cortex

Abstract: Astrocytes are the most numerous cell type in the central nervous system. When cultured, these cells express a wide variety of receptors for neurotransmitters. Nonetheless, it has yet to be firmly established that adult astrocytes in situ express receptors for neurotransmitters. In this report the technique of combined receptor autoradiography and immunocytochemistry has been applied to isolated astrocytes from adult animals to examine beta-adrenergic receptor (beta-AR) expression by these cells. It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…One-way analysis of variance showed no differences among astrocytes from the various brain regions, including reactive astrocytes from the ricin-treated MoV (F,,,,,,, = 1.2, P > 0.05). Salm and McCarthy (1989) demonstrated that astrocytes isolated from adult rat cerebral cortex express p-ARs. We confirmed their observations and also found p-ARs in astrocytes isolated from the striatum, trigeminal motor nucleus (MoV), and cerebellar cortex.…”
Section: Cw-ars On Astrocytesmentioning
confidence: 96%
“…One-way analysis of variance showed no differences among astrocytes from the various brain regions, including reactive astrocytes from the ricin-treated MoV (F,,,,,,, = 1.2, P > 0.05). Salm and McCarthy (1989) demonstrated that astrocytes isolated from adult rat cerebral cortex express p-ARs. We confirmed their observations and also found p-ARs in astrocytes isolated from the striatum, trigeminal motor nucleus (MoV), and cerebellar cortex.…”
Section: Cw-ars On Astrocytesmentioning
confidence: 96%
“…Glial cells may also be targets for noradrenergic innervation within the PVH as both alpha-and beta-adrenergic receptors have been localized in vitro to astrocytes in cultures derived from rat cortical and pituitary tissue (Bicknell et al, 1989;Lerea and McCarthy, 1989;Salm and McCarthy, 1989;Hatton et al, 1991). Another possible target for noradrenergic innervation are blood vessels within the PVH, which have been shown to receive monoaminergic innervation (Swanson et al, 1977).…”
Section: Dph-immunoreactive Innervation Of Vasopressin-and Oxytocin-imentioning
confidence: 99%
“…Hatton et al (1984) demonstrated that norepinephrine (NE) can alter astrocytic morphology in the hypothalamus and pituitary gland. Salm and McCarthy (1989) and Sutin (1991,1992) reported that most astrocytes isolated from various regions of adult rat brain exhibit p-adrenergic receptor binding sites and that the number of p receptor binding sites increase during astroglial hypertrophy. Likewise, glutamate uptake mechanisms were found predominantly in astrocytes in the brain (Martinez-Hernandez et al, 1977;Hertz, 1979;Danbolt et al, 1992).…”
Section: Mechanism Of the Glutamate Inhibition Of Glial Stellationmentioning
confidence: 99%